PENGETAHUAN KELUARGA TENTANG PENCEGAHAN DAN PENULARAN PENYAKIT TB PARU - Simanjuntak, Debora Enjelina; Legawati, Sri (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Pulmonary tuberculosis (TB) is a contagious infectious disease whose control is highly dependent on family participation. Family members living under the same roof as a patient are at high risk of transmission if they lack adequate understanding of the transmission mechanisms of Mycobacterium tuberculosis and preventive measures. Objective This study aims to describe the level of family knowledge regarding prevention efforts and transmission mechanisms of pulmonary tuberculosis in Cinta Jadi Village, Ujung Padang District. The research design used was descriptive quantitative. The study population included all families with members with pulmonary tuberculosis in Cinta Jadi Village. Sampling was conducted using a saturated sampling technique, resulting in 18 respondents. Data were collected using a questionnaire covering aspects of transmission and prevention, then processed through univariate analysis to generate frequency distributions and percentages. The study findings indicate that the majority of families' knowledge regarding pulmonary tuberculosis prevention is in the adequate category (68.6%), and knowledge regarding transmission is also in the adequate category (63.1%). Although most respondents understood that transmission occurs through the air, there were still gaps in understanding aspects of prevention, particularly regarding the benefits of sunlight exposure (vitamin D) and the use of clean water. Furthermore, regarding transmission, respondents were not fully aware that infants are at high risk of contracting pulmonary TB. Overall, the knowledge of families in Cinta Jadi Village regarding the prevention and transmission of pulmonary TB still needs to be improved, particularly in the dimensions of environmental health and home lighting. Health workers in Ujung Padang District are advised to optimize door-to-door outreach programs to strengthen preventive behaviors at the family level.